Analisis Daya Saing Usahatani Kelapa di Kabupaten Konawe Utara - Nikoyan, Anas (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
The aim of this study was to analyze the competitiveness of coconut farming in North Konawe District which was carried out in December 2019. Respondents in this study were 62 coconut farmers. Determination of the sample using the census method. Data analysis used is PAM analysis. The results showed that coconut farming in North Konawe Regency has competitiveness both competitively and comparatively. This can be seen from the value of the ratio of private costs and the ratio of the cost of domestic resources to coconut farming in North Konawe District, which is less than one.